The concept of legal protection of children as a narcotics courier - Martini; Made Warka; Otto Yudianto (Technium Social Sciences Journal, 2021)
The type of research used in this research is normative legal research. The regulation of legal protection for children in the judicial process is carried out starting from the level of investigation, investigation, prosecution, examination in court until the implementation of the court decision. During the judicial process, the rights of children must be protected by applicable law and therefore must be carried out consistently by parties related to the resolution of the problem of juvenile delinquents as regulated in Law No. 11 of 2012 concerning the Juvenile Criminal Justice System.